2021
DOI: 10.1155/2021/6670798
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bacterial and Fungal Human Respiratory Microbiota in COVID-19 Patients

Abstract: Recently, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the etiologic agent of coronavirus disease 2019 (COVID-19), has led to a worldwide pandemic with millions of infected patients. Alteration in humans’ microbiota was also reported in COVID-19 patients. The alteration in human microbiota may contribute to bacterial or viral infections and affect the immune system. Moreover, human’s microbiota can be altered due to SARS-CoV-2 infection, and these microbiota changes can indicate the progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 160 publications
2
43
0
Order By: Relevance
“…The cumulative results in our study demonstrated that PCV3 trend to low pathogenicity. Whether the synergy between PCV3 and bacterial/viral coinfections warrants further investigation [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cumulative results in our study demonstrated that PCV3 trend to low pathogenicity. Whether the synergy between PCV3 and bacterial/viral coinfections warrants further investigation [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Second, we tend to calculate the pooled prevalence based on WHO territorial office data and perform spatial analysis in several geographical districts to distinguish the high-risk area for viral coinfection [68][69][70][71][72][73][74][75][76], but this estimation may be unreliable because of the small number of studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the search of answer to the question of why this respiratory virus could affect humans in such a different way, the role of respiratory microbiota has been put on the spot. A very recent review about the role of respiratory microbiota in COVID-19 patients ( 95 ) concluded, based on previous evidence, that the dysbiosis in the microbiota in COVID-19 patients would potentially lead to infection or progression of the disease. However, studies on the characteristics of microbiome in COVID-19 patients are still scarce and conducted in a small number of patients to make them suitable for extrapolating conclusions ( 80 , 96 ).…”
Section: Nasopharyngeal Microbiome and Respiratory Diseasementioning
confidence: 99%